School, family and media teenagers sources of sexual information about sex and sexuality - San Juan, Ivy Karen T.
This study explored the knowledge and information sources of teenagers regarding adolescents' sexuality. Specifically, it identified the level of knowledge of teenagers about adolescent's sexuality in the areas of contraception, sexual health risks, and pregnancy, as well as the sources of students about sexuality. A qualitative research method was used that relied on the answers of respondents through an interview and by answering the research-made survey questionnaire. There were 20 student-respondents puposively selected from private school in Cavite. Results show that there is adequate knowledge on the third year and fourth year high showed that there is adequate knowledge on the third year and fourth year high school respondents on areas of Contraception and Sexual Health Risks. On the other hand, for the lower level, that is the first and second year high school-respondents, their knowledge on contraception and sexual health risks is partly inadequate. The sources of information of adolescent about sexuality were: the television, the school, which includes the teachers, the family, reading materials (i.e. newspapers and magazines), the radio and friends of peers. Acquired Immune Deficiency Syndrome (AIDS), a sexual health risk pinpointed by the most of the respondents as effect of unsafe sex, was learned through watching television documentaries featuring such topics. School was perceived as source of sexuality information, having sex education as part of the secondary curricula. The family was identified as the last source of information for adolescents. Both the parents and the children are ashamed, if not afraid, to involve themselves in discussion especially in sexuality-related issues and concerns. The use of condom, which was learned from the teachers and advertisements were perceived as the most effective methods of safe sex. The aspects of sexuality that the adolescents want to know were: the sexual health risks, particularly sexually-transmitted diseases (STD) as it related to safe sex; the strategies in resisting the temptation to engage in pre-marital sex (PMS); and the birth control methods. On the other hand, some adolescents do not want to know topics that cover the sexual act and the different sexual positions or style at this point. A majority of the student-respondents, however, would prefer to know all about sexuality; believing it would keep them aware and safe. It is recommended that parents should improve more in opening the communication between the parents and their children and recognizing the significance of sex education to their children's development. This also calls for the media, to be more responsible in providing shows that may contain pornographic, obscene movies and pictures that can have negative effect onto the children. In addition, sex education program should be taught when children start to inquire about it, and be given a sound and relevant information for their awareness and safety. It is interesting to pursue a study exploring the influence of religion as another source of information and how it can contribute to values clarification. Also, there is a need to determine what type of training intervention, or support environment that will be more effective in promoting appropriate behavior towards sex.